Strategi Pemasaran Holistik Starbucks dari Cangkir ke Komunitas - Ni Nyoman Retno Arthasa; Asep Saefurahman (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to analyze the holistic marketing strategy implemented by Starbucks, focusing on the approach from "cup to community." Starbucks not only markets its products as drinks, but also as a holistic life experience through the integration of product, service and community aspects. This holistic approach involves multiple dimensions of marketing, including relationship marketing, internal marketing, and social marketing, combined with technological innovation and desire. Starbucks builds emotional connections with consumers through loyalty programs, social initiatives and culturally relevant campaigns. This study provides insight into how a holistic strategy can create added value for brands, strengthen customer loyalty and increase social impact.